Tuning the Selectivity of Photocatalytic Synthetic Reactions Using Modified TiO2 Nanotubes - Tripathy, Jyotsna; Lee, Kiyoung; Schmuki, Patrik (Angewandte Chemie International Edition, 2014)
Differently modified TiO2 nanotubes were used to achieve a drastic change in the selectivity of a photocatalytic reaction. For the photocatalytic oxidation of toluene, depending on the electronic properties of TiO2 (anatase, rutile, Ru-doped), a strong change in the main reaction product (namely benzoic acid versus benzaldehyde) can be achieved, and certain undesired reaction pathways can be completely shut down.
EAM Import::2019-03-13